Use of high frequency supraglottic jet ventilation for microdirect laryngoscopy with CO2 laser treatment of subglottic stenosis. Issue 2 (August 2017) - Hussain, Adnan; Kupfer, Robbi; Healy, David; Schechtman, Samuel A.
Abstract : Abstract : Jet ventilation has been established as a method for both ventilation and oxygenation during airway surgery, and as a rescue airway technique in emergent airway management. It is essential for facilitating surgical treatment of subglottic stenosis, providing the surgeon with an unobstructed surgical view. Still considered an unsecure airway, and with high pressure and high frequency delivery of oxygen, jet ventilation can lead to several complications not experienced with endotracheal intubation. This case report describes benefits, approaches, and complications of mechanical to jet ventilation for subglottic stenosis, along with our institutional practices for this specialized airway management technique.